2009
DOI: 10.1007/s12552-009-9016-0
|View full text |Cite
|
Sign up to set email alerts
|

The Joint Effects of Offender Race/Ethnicity and Sex on Sentence Length Decisions in Federal Courts

Abstract: The current study examined the main and interactive effects of offender race/ethnicity and sex on sentence length decisions for drug offenders convicted in three federal courts located in Iowa, Minnesota, and Nebraska. The additive model showed that females received shorter prison sentences than similarly situated male offenders, but there were no differences between white offenders and minority offenders. However, when the data were partitioned by sex, black males were found to receive lengthier prison terms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 72 publications
1
24
0
2
Order By: Relevance
“…Others have also observed that Black and White women are equally likely to be incarcerated (Bickle & Peterson, 1991;Spohn & Beichner, 2000;Spohn & Spears, 1997;Steffensmeier & Demuth, 2006). There also appear to be no differences in the length of prison sentences given to White, Black, and Hispanic females (Brennan & Spohn, 2009; see also Crew, 1991;Steffensmeier & Demuth, 2006). And, in two studies that assessed differences in overall sentence severity, Black and White women received similar punishments (Farnworth & Teske, 1995;Kruttschnitt, 1984).…”
Section: Prior Empirical Researchmentioning
confidence: 96%
See 1 more Smart Citation
“…Others have also observed that Black and White women are equally likely to be incarcerated (Bickle & Peterson, 1991;Spohn & Beichner, 2000;Spohn & Spears, 1997;Steffensmeier & Demuth, 2006). There also appear to be no differences in the length of prison sentences given to White, Black, and Hispanic females (Brennan & Spohn, 2009; see also Crew, 1991;Steffensmeier & Demuth, 2006). And, in two studies that assessed differences in overall sentence severity, Black and White women received similar punishments (Farnworth & Teske, 1995;Kruttschnitt, 1984).…”
Section: Prior Empirical Researchmentioning
confidence: 96%
“…Overall, there is little empirical support for the theoretical notion that leniency at the sentence stage is reserved only for White women. Instead, findings from studies that have examined the combined influence of race/ethnicity and gender suggest that female offenders are likely to receive more lenient sentences than male offenders of the same race/ethnicity (Albonetti, 1997;Brennan & Spohn, 2009;Doerner & Demuth, 2010;Freiburger & Hilinski, 2009;Gruhl, Welch, & Spohn, 1984;Spohn et al, 1985;Steen et al, 2005;Steffensmeier & Demuth, 2006). There is also support for the notion that White women are treated more leniently than White men, Black men, and/or Hispanic men (Curry & Corral-Camacho, 2008;Spohn & Beichner, 2000;Spohn & Spears, 1997;Steffensmier & Demuth, 2006).…”
Section: Prior Empirical Researchmentioning
confidence: 99%
“…Between 1974 and 2000, the correctional population in the United States grew by more than 150%, with racial and ethnic minorities 4 to 6 times as likely as Whites to be sentenced to prison (Alexander, 2012). Although these disparities have been well documented in prior research (Bontrager, William, & Chiricos, 2005; Demuth & Steffensmeier, 2004; Feldmeyer, Warren, Siennick, & Neptune, 2015; Steffensmeier & Demuth, 2006), limited attention has been focused on understanding racial/ethnic disparities among female defendants (see Brennan & Spohn, 2009). The select set of studies that have explored how race and ethnicity affect sanctions among women generally offer mixed results.…”
Section: Introductionmentioning
confidence: 98%
“…First, the sample is limited to data on female felony sentencing events to explore how the combined effects of race, ethnicity, and gender influence punishment decisions (see also Belknap, 1996; Farnworth & Teske, 1995; Steffensmeier & Demuth, 2006). Indeed, Brennan and Spohn (2009) underscore the importance of assessing the intersection of race, ethnicity, and gender because it allows scholars to determine whether all minority female offenders are given more severe punishments compared with similarly situated Whites. In line with this focus, Steffensmeier and Demuth (2006) examined sentencing outcomes in 54 counties throughout the United States and generally found that White women were less likely to be incarcerated than all other combined racial/ethnic and gender categories.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation